Aplicação de CLEA de β-amilase de cevada na produção de maltose a partir de amido residual do bagaço de mandioca em reator de fluxo em vórtices - Silva, Rafael de Araujo (2015)
Cassava is cultivated worldwide, being Brazil the fourth largest producer. The root industrial processing in the country, aiming to obtain mainly flour and starch, generates carbohydrate-rich residues (e.g., starch, cellulose, and hemicellulose), which could be used to produce value-added products by enzymatic route, mainly using immobilized enzymes that are more operationally stable, allowing to be easily recovered and reused in the process. Thus, this work aimed the biotransformation of residual starch from cassava processing in maltose, using immobilized β-amylase in a Couette–Taylor–Poiseuille vortex flow reactor, which can promote perfect mixture under lower shear stress in the reactional medium compared to the conventional stirred-tank reactor. Cassava bagasse and peel of two starch-processing industries from São Paulo State were physicalchemically characterized and showed about 47% and 55% (dry mass) of residual starch, respectively. The starch was enzymatically extracted from the residues using a α- amylase, followed by maltose production catalyzed by immobilized barley β-amylase. Among the immobilization methods studied in this work, the best one for β-amylase was protein aggregation using bovine serum albumin (BSA) or soybean protein (PS) as protein feeder, followed by cross-linking with glutaraldehyde (CLEA technique). This protocol yielded immobilized β-amylase with 82.67% and 53.26% of recovered activity, respectively. Besides, the CLEAs were highly stables at 40oC, retaining more than 80% of the initial activity after 12 hours. The maltose syrup production from starch was performed using a Couette–Taylor–Poiseuille vortex flow reactor, in order to evaluate the β-amylase CLEAs (in this case CLEA of β-amylase prepared with soybean protein, here named CLEA-β-PS). It was achieved around 70% of maltose conversion in a short reaction time (4 hours), showing that is viable the use of residual starch as raw material for the production of maltose catalyzed by β-amylase CLEA in a Couette–Taylor– Poiseuille vortex flow reactor.